Parents' Ability To Stimulate The Psychosocial Development Of School-Aged Children - Rahayu, Desi Ariyana; Sari, Cahya Puspita; Mubin, Mohamad Fatkhul; Hidayati, Eni (South East Asia Nursing Research, 2024)
Background: WHO reported that the incidence of growth and developmental disorders in children remains high. In Southeast Asia, 28.7% of children experience growth and developmental disorders, and Indonesia ranks third in Southeast Asia with a prevalence of developmental delay in children reaching 5% to 10%. This study aims to identify parental abilities in stimulating psychosocial development in school-aged children.Method: This study employed a quantitative research design with a descriptive method. The sample consisted of 114 students from grades 2, 3, 5, and 6 at Kedungmundu Public Elementary School. The sampling procedure utilized non-probability sampling with purposive sampling technique.Result: The majority of children have not achieved the tasks of psychosocial development in school-aged children, with 62 children (54.4%) falling into this category, while 52 children (45.6%) have achieved these tasks. The majority of parents have suboptimal abilities in stimulating the development of school-aged children, with 59 parents (51.8%) falling into this category, while the remaining have optimal abilities in stimulating the development of school-aged children, with 55 children (46.2%). Regarding responses to stimulating the development of school-aged children, the majority of aspects have been achieved with an average percentage of 81.1%, while the average percentage of aspects not achieved is 18.9%. The highest percentage of achieved aspects is in the spiritual aspect, with a percentage of 95.6%, while the highest percentage of aspects not achieved is in the psychosocial aspect, with a percentage of 42.1%.